PENGARUH PENERAPAN METODE EDUTAIMENT TERHADAP HASIL BELAJAR SISWA MATERI BENTUK ALJABAR SMPN 02 SEGEDONG - Aisyah, Aisyah; Hartoyo, Agung; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is an experimental study with the design of posttest-Only control Group Design which aims to see the difference in the outcome of experimental class learning and control class. The experiment class was given an edutainment treatment method and a control class with expository methods. The Edutainment method in this study is a learning method that combines learning with the game while the Expository method is the method used by the school teacher. The population of this study is grade VII SMPN 02 Segedong. Sampling of research with Random Sampling technique. The data collection technique is an essay-shaped study (posstest) test that has been validator and tested by students of VIIB Junior high School Al-Fityan Pontianak. The results showed the percentage of the student's satisfaction with the Edutainment method higher than 62.5% with an average value of 74.7. Whereas with expository method of the percentage of submission 20% with an average value of 61.24. From the result of T test calculation with SPSS 16 obtained the value of SIG. (2-tailed) amounting to 0.00 to 0.00 < 0.05 Then there is a difference of learning outcomes between students of experiment class and control class. Keywords: Algebraic, Edutainment Method, Expository Method, Learning Result